Enhanced electrical conductivity and structural, mechanical characterization of standalone poly(vinyl alcohol)‐graphite nanoplatelets composite films. Issue 10 (4th October 2020) - Janeesh, G. M.; Meera, V.; Shalom, A. M.; Rajan Babu, D.; Nambi Raj, N. Arunai; Sreekanth, M. S.; Siva, V. Samba; Sumangala, T. P.
Abstract: Polymer based nanocomposites are gaining attention in various fields of science and technology due to its tunable properties. In this work, we report for the first time, the preparation and study on electrical and mechanical properties of standalone poly(vinyl alcohol) (PVA) based graphite nanoplatelet (GnP) composite films using modified film casting technique. Our modified tape casting method can produce films with uniform thickness, and uniform dispersion of filler deprived of pinholes. This technique is scalable for the mass production of polymer composite films for device application. We have obtained a significant enhancement in the electrical conductivity of 9 orders of magnitude and a maximum value of 0.143 S/m using PVA–GnP composites. To the best of our knowledge, this increase is the highest among the reported values for PVA–GnP composite films. However, a reduction in crystallinity and tensile strength can be seen with the addition of GnP fillers. The maximum tensile strength obtained for PVA–GnP composite films was 15 MPa and is adequate for use in electronic applications and devices. The effect of filler addition in PVA is discussed in detail. Abstract :